Are epilepsy patients bypassing primary care? A cross-sectional study from India. (August 2018) - Kumar, Shrawan; Singh, Mamta Bhushan; Kumar, Amit; Shukla, Garima; Padma Srivastava, M.V.; Goyal, Vinay; V.Y., Vishnu
Highlights: Only 60% epilepsy patients need to be managed in tertiary care. The remaining 40% patients may be taken care of at primary or secondary care levels. Referral system essential to ensure suitability of patients presenting to tertiary care. Adequate triaging of epilepsy patients to different care levels will improve access. Abstract: Purpose: Lack of epilepsy primary and secondary care and an arbitrary referral system causes many epilepsy patients to seek tertiary care even when they may not need it. This causes overcrowding, increased waiting times and also compromises the quality of tertiary care. We conducted this study to identify what proportion of epilepsy patients presenting to tertiary care actually needed it. Methods: To test appropriateness of candidacy for tertiary care, we formulated Modified NICE criteria (MNC) based on NICE criteria. Modified NICE criteria were used to dichotomize participants into two groups: a) those who needed tertiary care and b) those who did not need tertiary care. We also looked at agreement between MNC and original NICE criteria. Results: Four hundred and twenty two patients were recruited. According to the MNC, 240 patients (57%) qualified for tertiary care while 182 (43%) did not. The agreement between MNC and original NICE criteria was 86.7%, kappa 0.73(95% CI 0.66–0.79, p < 0.001). The most frequently cited reason for seeking tertiary care was 'Unsatisfactory response to treatment', although; many of these patients were actually non-adherent to treatment. Amongst variables that predicted non-eligibility for tertiary care, the most important was not having been referred. Conclusion: Many epilepsy patients seeking tertiary care do not need it. Access and quality of epilepsy care can be improved if there is a rational and need-based distribution of patients between primary, secondary and tertiary care. Referral systems also need to be developed and used to transition patients from one level of care to another.